Temporal dynamic effects of meteorological factors and air quality on the physical health of the older adults in Shenzhen, China - Jiang, Shuai; Han, Chuanliang; Ma, Yue; Ji, Jiajia; Chen, Guomin; Guo, Yinsheng (Frontiers in Public Health, 2024)
Meteorological and environmental factors can affect people's lives and health, which is crucial among the elderly. However, it is currently unclear how they specifically affect the physical condition of elderly people. We collected and analyzed the basic physical examination indicators of 41 elderly people for two consecutive years (2021 and 2022), and correlated them with meteorological and environmental factors. Partial correlation was also conducted to exclude unrelated factors as well. We found that among the physical examination indicators of the elderly for two consecutive years, five indicators (HB, WBC, HbAlc, CB, LDL-C) showed significant differences across the population, and they had significantly different dynamic correlation patterns with six meteorological (air pressure, temperature, humidity, precipitation, wind speed, and sunshine duration) and seven air quality factors (NO2, SO2, PM10, O3-1h, O3-8h, CO, PM2.5). Our study has discovered for the first time the dynamic correlation between indicators in normal basic physical examinations and meteorological factors and air quality indicators, which will provide guidance for the future development of policies that care for the healthy life of the elderly.